Karakterisasi Selulosa dan Selulosa Asetat dari Limbah Cangkang Biji Pala (Myristica Fragransi) Aceh Selatan - Bhayu Gita Bhernama; Nurhayati; Surya Adi Saputra; Jihan Amalia (Jurnal Riset Kimia, 2023)
Nutmeg seed shell waste contains 21.34% cellulose, 12.93% lignin, 53.67% crude fiber, 6.16% ash, 0.11% phenol, and 0.38% carbonyl. The content of cellulose and lignin in the nutmeg shell waste is quite large, so it can be used as something of value. Cellulose can be synthesized into cellulose acetate. The use of cellulose acetate is very diverse, such as in the film industry, biodegradable plastics, paper coatings, metals, and glass, as an adhesive for topographic films as the main raw material in membrane synthesis processes. Therefore, it is necessary to characterize cellulose and cellulose acetate from nutmeg shell waste (Myristica fragrance) in South Aceh. The method used is in the form of cellulose isolation using the soxhletation process, then bleaching and hydrolysis processes are carried out, then it is synthesized into cellulose acetate. Characterization of cellulose by determining % yield, cellulose content, ash content, moisture content, FTIR, XRD. Characterization of cellulose acetate by determining the acetyl content and FTIR. The characterization results obtained ash content of 3.04%, moisture content of 15.55%, yield of 35.36% and 5.29% cellulose content. XRD characterization obtained a diffractogram peak at an angle of 2θ = 22.2111o, a crystallinity of 96% and a crystal size of 0.5292 nm. Characterization of the functional groups of cellulose in the form of stretching O-H, C-H and C-O groups which are at wave numbers 3331.04 cm-1, 2871.29 cm-1 and 1024.96 cm-1. Functional groups of cellulose acetate in the form of O-H, C=O, acetyl C-O, bent C-H and C-O groups are at wave numbers 3348.82 cm-1, 1719.61 cm-1, 1227.23 cm-1, 1369.50 cm-1 and 1028.62. The acetyl content is 39.18% and the degree of substitution is 2.65%.